PENGARUH VARIASI PENAMBAHAN GLUTARALDEHID DAN GLISEROL TERHADAP KARAKTERISTIK HIDROGEL KITOSAN - nautillus, i made mateo; Arnata, I Wayan; Mahaputra Wijaya, I Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
This study aims to determine the addition of glutaraldehyde as a crosslinking agent and glycerol as a plasticizer to produce chitosan hydrogel with the best characteristics. This study used a factorial Randomized Block Design with three treatment factors:  the addition of glutaraldehyde (1gr, 2gr, and 3gr w/w) and the addition of glycerol (1gr, 2gr, and 3gr w/w). The variables observed were thickness, adsorption, tensile strength, and elongation at break. The results showed that added glutaraldehyde and glycerol significantly affected thickness, adsorption, tensile strength, and elongation of chitosan hydrogel. Based on the result, the best characteristics of the chitosan-glutaraldehyde-glycerol hydrogel are shown with the addition of 3 gr glutaraldehyde and 1 gr glycerol, which as value of 0.288±0.005 thickness, 1403.13±200.51 adsorption, 1.49±0.03 tensile strength, 26,64±0.21 elongation at break